2018
DOI: 10.1111/bph.14352
|View full text |Cite
|
Sign up to set email alerts
|

PEP06 polypeptide 30 exerts antitumour effect in colorectal carcinoma via inhibiting epithelial–mesenchymal transition

Abstract: PEP06 is a polypeptide that inhibits the growth and metastasis of colon cancer through its RGD motif binding to integrin αvβ3, thereby down-regulating miR-146b-5p to inhibit EMT in vitro and in vivo. It might have potential as a therapeutic for CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 63 publications
2
23
0
1
Order By: Relevance
“…Among the diagnostic candidates, miR-146b-5p is the most intensively investigated biomarker. Numerous studies have demonstrated that miR-146b can be stably detected in serum or plasma and has the potential to be the novel diagnostic biomarker for diseases other than thyroid cancer (Bookland et al, 2018), while also playing a controversial role in the initiation and development of colorectal cancer, leukemia, and glioma (Li et al, 2013;Zhang et al, 2016;Yu et al, 2018;Jia et al, 2019). In line with the previous publication, plasma exosomal miR-146b-5p, along with another five newly defined miRNA biomarkers, were also eligible for early diagnosis of thyroid nodules in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the diagnostic candidates, miR-146b-5p is the most intensively investigated biomarker. Numerous studies have demonstrated that miR-146b can be stably detected in serum or plasma and has the potential to be the novel diagnostic biomarker for diseases other than thyroid cancer (Bookland et al, 2018), while also playing a controversial role in the initiation and development of colorectal cancer, leukemia, and glioma (Li et al, 2013;Zhang et al, 2016;Yu et al, 2018;Jia et al, 2019). In line with the previous publication, plasma exosomal miR-146b-5p, along with another five newly defined miRNA biomarkers, were also eligible for early diagnosis of thyroid nodules in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because this upregulation was observed at the protein level, some of the included proteins might likely be converted to actionable targets for the treatment of mesenchymal CRCs of CMS4. Indeed, previous studies of various colon carcinoma models showed that the suppression of EMT may be achieved by integrin (included in ECM receptor interaction pathway) interaction disruptors [77]. Other ECM receptor interaction pathway proteins (Fig 4) could potentially be good candidates for targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Desiccated PEP06 was kindly provided by the Department of Pharmacology, Harbin Medical University. For in vitro studies, PEP06 was prepared as described previously and applied at low, medium and high concentrations (50, 100, and 200 μg/mL) 28 . Glucose solution (5%) was used in the vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…Terminal fusion of RGDRGD hexapeptide to the 1–24 amino acid residues of NH 2 -fragment of endostatin is thought to result in amplified therapeutic potential of PEP06 polypeptide 30 due to direct targeting of cancer-specific cellular processes26, 27. Recently, our colleagues have demonstrated a strong antitumor effect of PEP06 on colorectal cancer mediated through interactions between RGD motifs and α v β 3 integrins in tumor cells 28 . We speculated that PEP06 polypeptide as RGD-derivative from endostatin might possess direct therapeutic efficacy against OSCC in the context of interference with clustered organization of cancer cells.…”
Section: Introductionmentioning
confidence: 99%